Functional Connectivity Differences in the Resting-state of the Amygdala in Alcohol-dependent Patients with Depression - Sun, Fengwei; Kong, Zhi; Tang, Yun; Yang, Jihui; Huang, Gengdi; Liu, Yu; Jiang, Wentao; Yang, Mei; Jia, Xiaojian (Academic radiology, 2024)
The mechanism of comorbidity between alcohol dependence and depressive disorders are not well understood. This study investigated differences in the brain function of alcohol-dependent patients with and without depression by performing functional connectivity analysis using resting-state functional magnetic resonance imaging. A total of 29 alcohol-dependent patients with depression, 31 alcohol-dependent patients without depression and 31 healthy control subjects were included in this study. The resting-state functional connectivity between the amygdala and the whole brain was compared among the three groups. Additionally, we examined the correlation between functional connectivity values in significantly different brain regions and levels of alcohol dependence and depression. The resting-state functional connectivity between the left amygdala and the right caudate nucleus was decreased in alcohol-dependent patients. Additionally, the resting-state functional connectivity of the right amygdala with the right caudate nucleus, right transverse temporal gyrus, right temporal pole: superior temporal gyrus were also decreased. In alcohol-dependent patients with depression, not only was functional connectivity between the above brain regions significantly decreased, but so was functional connectivity between the right amygdala and the left middle temporal gyrus. Also, there was no significant correlation between the resting-state functional connectivity values in statistically significant brain regions and the levels of alcohol dependence and depression. The impairment of the functional connectivity of the amygdala with caudate nucleus and partial temporal lobe may be involved in the neural mechanism of alcohol dependence comorbidity depressive disorders.